2019
DOI: 10.3847/1538-4357/ab50b6
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Solar Coronal Mass Ejections in the Extreme-ultraviolet Passbands

Abstract: So far, most studies on the structure of coronal mass ejections (CMEs) are conducted through white-light coronagraphs, demonstrating that about one third of CMEs exhibit the typical three-part structure in the high corona (e.g., beyond 2 ), i.e., the bright front, the dark cavity, and the bright core. In this paper, we address the CME structure in the low corona (e.g., below 1.3 )… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 49 publications
5
24
0
Order By: Relevance
“…A similar result was also reported by Bein et al (2011) but it must be noted that their numbers suffered from projection effects and their numbers were obtained by combining Extreme Ultraviolet (EUV) and White Light (WL) observations which brings in an additional ambiguity of whether the same physical feature is being tracked in EUV and WL (for a discussion, see Song et al 2019, and references therein), as the former corresponds to the temperature structure of a CME while the later corresponds to the density structure (Ying et al 2020). In our work, we do away with both of these limitations, as our measured numbers are in 3D and the measurements are done uniquely in WL.…”
Section: Resultssupporting
confidence: 73%
“…A similar result was also reported by Bein et al (2011) but it must be noted that their numbers suffered from projection effects and their numbers were obtained by combining Extreme Ultraviolet (EUV) and White Light (WL) observations which brings in an additional ambiguity of whether the same physical feature is being tracked in EUV and WL (for a discussion, see Song et al 2019, and references therein), as the former corresponds to the temperature structure of a CME while the later corresponds to the density structure (Ying et al 2020). In our work, we do away with both of these limitations, as our measured numbers are in 3D and the measurements are done uniquely in WL.…”
Section: Resultssupporting
confidence: 73%
“…Since the core has been identified as the flux rope in white-light images of CMEs (e.g. Howard et al 2017;Song et al 2019), we use its heliocentric distance, about 3 R , to estimate the height of the flux rope. From the location of the two radio sources at high frequencies (432 MHz) we infer that the two legs of the flux rope were distant by about 14 • .…”
Section: F3 Correlated Evolution Of Brightness Temperatures In the mentioning
confidence: 99%
“…A coronal mass ejection (CME) is generally understood to comprise a magnetic flux rope, which at some time starts to rise into the high corona (e.g. Démoulin & Aulanier 2010;Howard et al 2017;Song et al 2019). It leaves behind a stressed magnetic field that will re-arrange itself over several hours.…”
Section: Introductionmentioning
confidence: 99%
“…The cavity and core have been considered as the MFR cross section and erupted filament, respectively, for several decades. However, recent studies clearly demonstrated that both the filaments and hot channel MFRs can appear as the bright core [13][14][15][16]. The hot channels are first revealed through extreme ultraviolet passbands sensitive to high temperatures (e.g., 131 and 94 Å) [17], and they can also be observed in hard X-ray [18] and microwave [19] images.…”
Section: Introductionmentioning
confidence: 99%
“…The hot channels are first revealed through extreme ultraviolet passbands sensitive to high temperatures (e.g., 131 and 94 Å) [17], and they can also be observed in hard X-ray [18] and microwave [19] images. Researchers also suggest that the dark cavity corresponds to a low-density region with a sheared magnetic field in the early eruption stage [16].…”
Section: Introductionmentioning
confidence: 99%